The Application of the Retroactive Principle in Decisions of State Administrative Officials to Realize Legal Utility - Ridwan A. Jula; Fenty U. Puluhulawa; Erman I. Rahim (International Journal of Law, Crime and Justice, 2025)
This study examines the application of the retroactive principle in the issuance of State Administrative Decisions (KTUN) by regional administrative officials amid digitalization in public services. The research aims to examine the legal basis of retroactive application within administrative law and to identify appropriate mechanisms to ensure its benefit for public administration and society. Using a normative juridical method with statutory and conceptual approaches, the research is supported by literature studies on legal documents and regulations. The findings indicate that, under Indonesian administrative law, the retroactive application of KTUN is legally permissible if it meets specific conditions outlined in the Law on Government Administration—primarily to prevent greater harm and/or to protect citizens’ rights. Retroactive KTUN may address discrepancies between the timing of decision issuance and actual administrative activities, especially in a digital governance environment. The study concludes that to ensure legal certainty and accountability, such application must be based on formal mechanisms, including the development of standard operating procedures (SOPs) and the issuance of regional head regulations as normative foundations. These measures are essential to institutionalize retroactive KTUN and ensure its use aligns with principles of legal certainty, public benefit, and good governance in regional government administration.